Modern strategies for the treatment of psychoemotional stress in patients with heart coronary disease after myocardial revascularization - Holdovskyy, B. M.; Filimonova, I. V.; Potalov, S. O.; Serikov, K. V.; Lelyuk, D. V.; Filimonov , R. V. (Modern medical technology, 2019)
Coronary heart disease in many countries of the world, including in Ukraine, causes high rates of morbidity, disability and mortality. The study of factors affecting the occurrence, course, prognosis and effectiveness of drug therapy for coronary artery disease is important and relevant. One of such factors is the psychological disorders of the anxiety-depressive spectrum, which often occur in patients with myocardial infarction and after coronary artery bypass grafting; therefore, such patients should be carefully examined for affective disorders and receive appropriate drug therapy. Purpose of the study. Improvement of diagnosis and optimization of patients treatment with ischemic heart disease with concomitant anxiety-depressive disorders after myocardial revascularization. Material and methods. The results of the study are based on survey data and dynamic observation of 95 patients with coronary heart disease, postinfarction cardiosclerosis after myocardial revascularization. The patients underwent examination during the initial examination and after 12 weeks. Results of the study and their discussion. In the study of the psychoemotional state in the patients examined after the treatment, a significant decrease in anxiety manifestations was revealed by 36,4% against the group without fluvoxamine, where there was no significant difference before and after treatment. The manifestations of depressive disorder in the fluvoxamine group significantly decreased after treatment by 45,8 (HADS) and by 47,0% (Beck), in contrast to the group without fluvoxamine, where there was no significant difference before and after treatment. Conclusions. Thus, it has been proved that with the addition of fluvoxamine to combined therapy for patients with ischemic heart disease, postinfarction cardiosclerosis after revascularization of the myocardium shows a more pronounced decrease in the manifestations of anxiety-depressive disorder.